KAJIAN PENGARUH KARAKTERISTIK MEKANIK DAMPER LELEH BAJA TERHADAP RESPON BANGUNAN AKIBAT GAYA GEMPA DENGAN MENGGUNAKAN ANALISIS RIWAYAT WAKTU - Eka Desy Pratiwi (Jurnal Teknik Sipil USU, 2013)
ABSTRACT The earthquake force that shake the building cause damage to the structure. This damage occurs as a result of energy dissipation processes in building elements. The amount of damage on conventional building is generally influenced by two factors: the earthquake characteristics (acceleration), and building characteristics (time vibration, stiffness, ductility building materials, etc). In contrary the unconventional building which has been specifically modified using the damper will be influenced by additional factors such as the damper characteristics (stiffness, yield displacement, yield force). In this paper the model of two-dimensional structure (three-bay, six-story) of steel moment resisting frame with and without damper are investigated under imperial parachute earthquake ground motion. The response parameters such as displacement, acceleration and base shear are given and compared in the table and graph. Finally the result obtained that placing damper in the building can reduce response parameters. Keywords: Metallic yielding damper, ADAS